Reproductive Biology of a Medicinal Orchid Satyarium Nepalense (Orchidaceae) in the Nepalese Himalayas - Paudel, Babu Ram; Poudel, Brihaspati (Himalayan Biodiversity, 2020)
Satyrium nepalense is a terrestrial medicinal orchid of the Himalayas. Although, the ecology and medicinal uses of this orchid is well known, little is known about its reproductive mechanism. In this study, we explored the natural history and reproductive biology of S. nepalense and tested their potential spatial variation. We observed the floral visitors and natural fruit set of S. nepalense at its two populations. We found that, despite the presence of outcrossing features, this orchid did not receive any diurnal floral visitors. The natural fruit set was very high (>90.0%) at both the sites, suggesting the possibility of autonomous selfing. This finding may have important implication for the further study to explore how autonomous selfing evolves in a member of the predominately outcrossing genus. Moreover, the finding of this study provides important insight to develop efficient protocol for its conservation.